2005
DOI: 10.1038/sj.leu.2403976
|View full text |Cite
|
Sign up to set email alerts
|

Human myeloma cells express the bone regulating gene Runx2/Cbfa1 and produce osteopontin that is involved in angiogenesis in multiple myeloma patients

Abstract: Osteopontin (OPN) is a multifunctional bone matrix glycoprotein that is involved in angiogenesis, cell survival and tumor progression. In this study we show that human myeloma cells directly produce OPN and express its major regulating gene Runx2/Cbfa1. The activity of Runx2/Cbfa1 protein in human myeloma cells has also been demonstrated. Moreover, using small interfering RNA (siRNA) to silent Runx2 in myeloma cells, we suppressed OPN mRNA and protein expression. OPN production in myeloma cells was stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
60
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 38 publications
7
60
0
2
Order By: Relevance
“…In an in vitro model of angiogenesis, OPN-immunodepleted CM from myeloma cells failed to induce a proangiogenic effect and an anti-OPN Ab blocked myelomainduced angiogenesis [74]. These observations support the potential role of OPN as a direct pro-angiogenic factor in MM.…”
Section: Matrix Metalloproteinasessupporting
confidence: 62%
See 1 more Smart Citation
“…In an in vitro model of angiogenesis, OPN-immunodepleted CM from myeloma cells failed to induce a proangiogenic effect and an anti-OPN Ab blocked myelomainduced angiogenesis [74]. These observations support the potential role of OPN as a direct pro-angiogenic factor in MM.…”
Section: Matrix Metalloproteinasessupporting
confidence: 62%
“…OPN expression by myeloma cells was also correlated with increased BM angiogenesis in MM patients. In particular, it has been demonstrated that OPN positive MM patients have a significantly higher MVD and number of microvessels per field as compared to OPN negative patients [74].…”
Section: Relationship Between Angiogenic Factors and Bm Angiogenesis mentioning
confidence: 99%
“…[2][3][4][5][6][7][8] The angiogenic switch in MM is mainly sustained by the overproduction of vascular endothelial growth factors (VEGFs) by MM cells and the BM microenvironment. 2,9,10 Other proangiogenic molecules, such as basic fibroblast growth factor, 11,12 interleukin-8 (IL-8), 13 angiopoietin-1 14 and osteopontin 15 are involved in the pro-angiogenic process. Hypoxia is a common feature of solid tumors and is associated with angiogenesis and malignant phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Runt-related transcription factor-2 regulation and transcriptional activity are linked with increased growth, invasion, and metastasis in breast cancer (Barnes et al, 2003), prostate cancer (Brubaker et al, 2003;Pratap et al, 2005), colorectal cancer (Wai et al, 2006), lymphoma, leukaemia and myeloma (Wotton et al, 2002;Castilla et al, 2004;Colla et al, 2005;Blyth et al, 2006).…”
mentioning
confidence: 99%